2020
DOI: 10.1111/nuf.12486
|View full text |Cite
|
Sign up to set email alerts
|

Mastectomy tattoos: An emerging alternative for reclaiming self

Abstract: Recent discourses within breast cancer and gendered studies literature suggest some women are challenging postmastectomy bodies as abject bodies. Tattooing is an emerging body project in contemporary society that can offer women who live disembodied from their postmastectomized body an alternative. We consider embodied health movements, a type of social movement, to explore how acquiring meaningful tattoo art over a mastectomized site can been seen as challenging hegemonic, gendered discourses of the female br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There is a corpus of research describing the negative emotional and psychological impacts of breast cancer mastectomy surgery and scarring and how that influences women’s body image and sense of self ( Brunet et al, 2022 ; Hopwood and Hopwood, 2019 ; Piot-Ziegler et al, 2010 ). An emerging research area has shown that artistically tattooing the post-mastectomy body has potential to positively influence or change that post-cancer embodied experience ( Reid-de Jong, 2022 ; Reid-de Jong and Bruce, 2020 ; Strübel and Jones, 2017 ). In an effort to contribute to that emerging area of interest, the current study aimed to explore how artistically tattooing mastectomy scars change how women perceive their post-cancer body and how women experienced their evolving self from these often confronting and highly medicalised experiences.…”
Section: Discussionmentioning
confidence: 99%
“…There is a corpus of research describing the negative emotional and psychological impacts of breast cancer mastectomy surgery and scarring and how that influences women’s body image and sense of self ( Brunet et al, 2022 ; Hopwood and Hopwood, 2019 ; Piot-Ziegler et al, 2010 ). An emerging research area has shown that artistically tattooing the post-mastectomy body has potential to positively influence or change that post-cancer embodied experience ( Reid-de Jong, 2022 ; Reid-de Jong and Bruce, 2020 ; Strübel and Jones, 2017 ). In an effort to contribute to that emerging area of interest, the current study aimed to explore how artistically tattooing mastectomy scars change how women perceive their post-cancer body and how women experienced their evolving self from these often confronting and highly medicalised experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Medical tattooing can also be used to address complications associated with necrosis, excess scarring, asymmetrical nipple areolas, and complete or partial loss of the nipple due to ap or graft techniques during surgery [22]. It is often pursued by patients and survivors independent of their physicians and surgeons to improve cosmetic outcomes and regain a sense of empowerment [21,22].…”
Section: Medical Tattooingmentioning
confidence: 99%
“…Medical tattooing in this context can signify a women's agency to reclaim their body and re ne concepts of the self, such as self-expression, identity, femininity, sexuality, healing, and transformation [21,22]. It can also serve to help survivors address any cosmetic complications (e.g., scarring, necrosis, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Specific wabi-sabi traditions, (eg, kintsugi) might have direct applications—for example, supporting patients who choose to embrace rather than erase their scars 6…”
Section: Physical Imperfectionmentioning
confidence: 99%